2014
DOI: 10.1111/1541-4337.12077
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Evaluate Uptake of Engineered Nanomaterials by the Alimentary Tract

Abstract: This article is one of a series of 4 that report on a task of the NanoRelease Food Additive project of the International Life Science Institute Center for Risk Science Innovation and Application to identify, evaluate, and develop methods that are needed to confidently detect, characterize, and quantify intentionally produced engineered nanomaterials (ENMs) released from food along the alimentary tract. This particular article focuses on the problem of detecting and characterizing ENMs in the various compartmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 83 publications
1
19
0
1
Order By: Relevance
“…There are 3 possible routes for ENPs to enter the human body: dermal exposure, inhalation, and the oral route of exposure (Crosera and others ; Sung and others ; Alger and others ). Although many studies have been reported on the dermal exposure and inhalation of ENPs, little is known about the exposure of ENPs via ingestion and whether the gastric fluid in the stomach can affect the toxicity of ENPs.…”
Section: Introductionmentioning
confidence: 99%
“…There are 3 possible routes for ENPs to enter the human body: dermal exposure, inhalation, and the oral route of exposure (Crosera and others ; Sung and others ; Alger and others ). Although many studies have been reported on the dermal exposure and inhalation of ENPs, little is known about the exposure of ENPs via ingestion and whether the gastric fluid in the stomach can affect the toxicity of ENPs.…”
Section: Introductionmentioning
confidence: 99%
“…The NanoRelease Food Additive project, coordinated by the International Life Sciences Institute (ILSI) Research Foundation Center for Risk Science Innovation and Application, is reviewing and developing methods to measure the release and uptake of intentionally engineered NMs from food matrices in the GI tract (Alger et al, 2014;Noonan et al, 2014;Singh et al, 2014;Szakal et al, 2014a,b). Food is naturally chemically complex and consists of biological polymers with dimensions in the nanometer size range.…”
Section: Introductionmentioning
confidence: 99%
“…The focus area of this article is analytical methods to identify, detect, and characterize ENMs in foods, including sample preparation techniques. The second and 4th articles in this series, respectively, describe methods to detect ENMs released into foods from food contact materials (Noonan and others ) and describe methods to characterize, detect, and study the behavior of ENMs introduced into the alimentary tract through dietary uptake (Alger and others ). While this particular article is capable of standing alone, due to the fact that some experimental methods may have utility in multiple areas relevant to the project's overall scope, some methods discussed within this article may have additional descriptive detail offered in other articles in this series.…”
Section: Introductionmentioning
confidence: 99%